The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1051/0004-6361/201937296
|View full text |Cite
|
Sign up to set email alerts
|

A new method for measuring the meteor mass index: application to the 2018 Draconid meteor shower outburst

Abstract: Context. Several authors predicted an outburst of the Draconid meteor shower in 2018, but with an uncertain level of activity. Aims. Optical meteor observations were used to derive the population and mass indices, flux, and radiant positions of Draconid meteors. Methods. 90 minutes of multi-station observations after the predicted peak of activity were performed using highly sensitive Electron Multiplying Charge Coupled Device (EMCCD) cameras. The data calibration is discussed in detail. A novel maximum likeli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…From atmospheric observations (Vojáček et al 2019;Vida et al 2020b) and in-situ measurements of dust at parent comets (Fulle et al 2016), it is known that masses of shower meteors are usually distributed according to a power-law distribution:…”
Section: Scaling the Flux To A Target Limiting Magnitude Or Massmentioning
confidence: 99%
“…From atmospheric observations (Vojáček et al 2019;Vida et al 2020b) and in-situ measurements of dust at parent comets (Fulle et al 2016), it is known that masses of shower meteors are usually distributed according to a power-law distribution:…”
Section: Scaling the Flux To A Target Limiting Magnitude Or Massmentioning
confidence: 99%
“…The cameras begin to show saturation effects near meteor magnitudes of +1. For example meteor images and more details about the system see Vida et al (2020).…”
Section: Optical Camerasmentioning
confidence: 99%
“…Distribution of peak magnitudes for iron (red) and the entire population as a whole. The effective survey completeness is to an absolute magnitude of +6 at low speeds using the methodology described in(Vida et al 2020), falling to +5 at 60 km/s.…”
mentioning
confidence: 99%
“…The period covered by our survey (2018-2021) includes several meteor shower outbursts. Unfortunately, the 2018 Draconid outburst (Egal et al 2018;Vida et al 2020c) was only observed from a single station as the network was still in development at the time (Vida et al 2018a). Nevertheless, several other outbursts were recorded; the associated mean radiants and orbital elements are given in Table 2.…”
Section: Meteor Shower Outburstsmentioning
confidence: 99%